Samuel Eliot Morison papers - Morison, Samuel Eliot, 1887-1976.
Journals relating to the oceanic theaters of World War II and to anti-submarine warfare. Research notebooks relate to Morison's writings. Journals contain wartime entries and a record of interviews with William H.P. Blandy; Andrew Browne Cunningham, Viscount Cunningham of Hyndhope; Royal E. Ingersoll; Douglas MacArthur; Sir Henry Ruthven Moore; Franklin D. Roosevelt; Raymond Ames Spruance; Harold R. Stark; Richmond Kelly Turner; and others. Topics include the battles of Casablanca, Guadalcanal, Kolombangara, and Pearl Harbor; and operations Dragoon, Galvanic, Neptune, Overlord, and Torch.
U.S. naval officer and historian.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: Blandy, William H. P. -- 1890-1954.; Cunningham of Hyndhope, Andrew Browne Cunningham, -- Viscount, -- 1883-1963.; Ingersoll, Royal E. -- 1883-1976.; MacArthur, Douglas, -- 1880-1964.; Moore, Henry Ruthven, -- Sir, -- 1886-1978.; Roosevelt, Franklin D. -- 1882-1945.; Spruance, Raymond Ames, -- 1886-1969.; Stark, Harold R. -- 1880-1972.; Turner, Richmond Kelly, -- 1885-1961.; Anti-submarine warfare; Guadalcanal, Battle of, Solomon Islands, 1942-1943.; Kolombangara, Battle of, Solomon Islands, 1943.; Operation Dragoon, 1944.; Operation Galvanic, 1943.; Operation Neptune; Operation Overlord; Operation Torch, 1942.; Pearl Harbor (Hawaii), Attack on, 1941.; World War, 1939-1945 -- Campaigns -- France; World War, 1939-1945 -- Campaigns -- Africa, North; World War, 1939-1945 -- Campaigns -- Solomon Islands; World War, 1939-1945 -- Naval operations; Casablanca (Morocco) -- History; Historians; Naval officers